ANALISIS DATA KOTA TANGGERANG BERDASARKAN KELOMPOK UMUR DAN JENIS KELAMIN TAHUN 2022 - Alvin Fajar Mutaqim; Bima Putra Aditya, Riza Fahlapi (ADISAM PUBLISHER, 2024)
This research aims to identify the methods used by the government in managing data based on age and gender. Data collection techniques based on the Tanggerang city statistics center agency. The results of the research obtained are that the government knows the population in the city of Tanggerang in 2022. And the results of research on the number of residents in the city of Tanggerang in 2022 use various forms of data presentation such as tables, bar charts, pie charts and line charts. Data management is carried out with the help of tables and Microsoft Excel software